Accrual-based earnings management and real activities manipulation to avoid losses: Evidence from unlisted public companies in Vietnam - Phạm Nguyễn Đình Tuấn; Trần Thị Bích Duyên (My University, 2020)
Accrual-based earnings management and real activities manipulation to avoid losses: Evidence from unlisted public companies in Vietnam
Keywords: Earnings management; Avoid losses; Unlisted companies